The Potential of Green Mussel Shells (Perna Viridis) As An Alternative Calcium Source In The Cement Industry - Rahman, Herliati; Fitriani, Firda; Wahyu Hendry K, Seventien (Al-Kimia, 2024)
Green mussel shells are a potential source of calcium oxide for the cement industry. As the largest producer of shells in Asia, with an annual production of 309,886 tons, Indonesia faces the challenge of shell waste amounting to 70% of the total shell weight. Therefore, optimizing green mussel shell waste (GMS) is crucial to reducing environmental pollution and promoting innovation in eco-friendly cement production. This study aims to extract calcium carbonate (CaCO3) from green mussel shells through a 4-hour calcination process at temperatures of 700°C, 800°C, and 900°C. Analysis using titrimetric and X-ray Fluorescence (XRF) methods shows that GMS flour's calcium oxide (CaO) content reaches 98.16%. XRD diffractograms at a calcination temperature of 900°C indicate CaCO3 phases consistent with ICDD data No. 01-070-9854, identified at 2θ: 29.4°; 32.21°; and 37.37° (100%). Compressive strength tests demonstrate that adding 10% green mussel shells can increase cement compressive strength by 2.3%. These findings support using green mussel shells as an alternative raw material in the cement industry. By maximizing shell waste utilization, the industry can reduce waste and promote more sustainable and environmentally friendly cement production, marking a significant step towards waste management innovation and green solutions in the construction industry.